Memetakan Kepuasan Konsumen Dan Implikasinya Terhadap Loyalitas Serta Pengelolaan Persediaan Di UMKM D’Shafa - Diki Ripandi; Ihsan Taufiqurrahman; Alifia Wardahesa Syaniah; Siti Fauziah; Ruth Angelica Sitorus; Khoirul Aziz Husyairi (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
MSMEs play an important role in the Indonesian economy but often face challenges in maintaining customer satisfaction and loyalty. Optimal customer satisfaction not only impacts loyalty but also affects the efficiency of inventory management. This study aims to map the influence of customer satisfaction on customer loyalty and its implications for inventory management in D'Shafa MSMEs using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. This research method adopts a survey design with data collected through questionnaires distributed to customers of D'Shafa MSMEs. Data analysis was conducted using the SEM-PLS technique to examine the relationships between customer satisfaction, loyalty, and inventory management. The results indicate that customer satisfaction has a positive and significant influence on customer loyalty. Additionally, customer loyalty positively impacts inventory management, with high loyalty driving efficiency in stock and demand management. These findings suggest that D'Shafa MSMEs should focus on improving customer satisfaction as a key strategy to enhance customer loyalty and optimize inventory management. This research contributes to understanding the dynamics of customer satisfaction and inventory management in the context of MSMEs and offers practical recommendations for more effective marketing and inventory management strategies.